2016
DOI: 10.1111/jth.13321
|View full text |Cite
|
Sign up to set email alerts
|

The role of microRNA‐27a/b and microRNA‐494 in estrogen‐mediated downregulation of tissue factor pathway inhibitor α

Abstract: To cite this article: Ali HO, Arroyo AB, Gonz alez-Conejero R, Stavik B, Iversen N, Sandset PM, Mart ınez C, Skretting G. The role of microRNA27a/b and microRNA-494 in estrogen-mediated downregulation of tissue factor pathway inhibitor a. J Thromb Haemost 2016; 14: 1226-37. Essentials• Estrogens are known to influence the expression of microRNAs in breast cancer cells.• We looked at microRNAs in estrogenic regulation of tissue factor pathway inhibitor a (TFPIa).• Estrogen upregulated microRNA-27a/b and micro-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 51 publications
0
17
1
Order By: Relevance
“…It was demonstrated that exosomal miRNA‐155, an onco‐miRNA, inhibits SOCS6, can activate STAT3 and elevate the expression of the genes involved in proliferation and differentiation of SKBR3 cells and MCF‐7, finally leading to resistance of BC cells to tamoxifen . Some studies reported that miRNA‐27a/b negatively affects the expression of TFPIa in MCF‐7 cells . TFPIa is an apoptosis inducer in BC cells .…”
Section: Exosomal Mirnas In Bc Drug Resistancecontrasting
confidence: 61%
“…It was demonstrated that exosomal miRNA‐155, an onco‐miRNA, inhibits SOCS6, can activate STAT3 and elevate the expression of the genes involved in proliferation and differentiation of SKBR3 cells and MCF‐7, finally leading to resistance of BC cells to tamoxifen . Some studies reported that miRNA‐27a/b negatively affects the expression of TFPIa in MCF‐7 cells . TFPIa is an apoptosis inducer in BC cells .…”
Section: Exosomal Mirnas In Bc Drug Resistancecontrasting
confidence: 61%
“…One of the miRs we found upregulated in MCF-7, miR-424, was also shown to be induced by 17-β-estradiol in at least two (95,96) of the multiple studies conducted in MCF-7. In some cases, ethanol induced upregulation is also seen after estrogen treatment, such as in miR-27a and b (96).…”
Section: Discussionmentioning
confidence: 61%
“…In some cases, ethanol induced upregulation is also seen after estrogen treatment, such as in miR-27a and b (96). The fact that ethanol affected any particular miR in this study did not necessarily coincide with affects on other miRs that would be expected to change comcomitantly if ethanol action were limited to one specific pathway such as the estrogenic pathway: thus upregulated miRs such as miR-107, miR-424, miR-570, miR-618, and miR-760 (95), miR-21 (28), miR-34b (97), miR-98 (98), miR-19A and miR-24 (96), miR-26a and b (99), miR-17 (100,101), miR-7 (102), or miR-190a (103); or downregulated miRs such as miR-16, miR-143, or miR-203 (104). Interestingly, the latter is the opposite of what we observed with ethanol.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of several hemostatic factors has been reported to be regulated by miRNAs [23,24] including key procoagulant factors and inhibitors of the coagulation pathway as well as plasminogen activator inhibitor-1, the main modulator of fibrinolysis [25][26][27][28][29][30][31][32][33][34][35][36][37] (Table 1 and Figure 1). In a recent study, Nourse et al (2018) [38] revealed that individual genes encoding key hemostatic factors can be targeted by multiple miRNAs, suggesting that miRNAs act cooperatively in the regulation of the hemostatic system.…”
Section: Introductionmentioning
confidence: 99%